Income and employment generation through ecofriendly utilisation of paddy straw for mushroom and vermicompost production - Mishra, S K; Prangya, Swatee; Sathpathy, B S; Lenka, S; Das, Lipi; Jena, Krutibasa; Jethy, Sonali (Indian Farming, 2022)
The enterprise-based module of NRRI-Farmer FIRST Programme has improved the livelihood as well as nutritional security of the several families by adopting production of mushroom and vermicompost. Mushroom cultivation has ensured enhancement of family income with less investment and high returns. By growing paddy straw mushroom 4000 beds/annum, a farmer is getting a net return of `300000.00 and 160 mandays employment per year. Mushroom farming has been introduced and propagated as an enterprise in the cluster which has resulted in additional family income adding to family nutrition. Besides, producing vermicompost by utilising mushroom spent generated from 4000 beds, a farmer can earn additional net income of `136000.00 and 80 mandays employment. The available surplus paddy straw can be used for commercial production of mushroom and vermicompost.